Investigations of nanocoolant based Al2O3 for improving cooling performance in hot press forming - Lim, Syh Kai (2018)
Hot press forming (HPF) to develop UHSS of boron sheet metals for vehicle inner body panels offers efficient fuel consumption in order to reduce carbon dioxide gas emissions by weight reduction and improves passenger safety because of its high mechanical properties. The sheet metal is heated up to austenitic temperature and then rapidly quenched in an enclosure dies in a certain quenching time to exhibit martensitic transformation phase. Currently, water is used as coolant in the HPF process to quench boron steels in a closed die with a cooling channel. However, to enhance the performance of HPF dies and increase the mechanical properties of hot pressed boron steel, the fluid with better thermal properties will be used instead of normal water. During the quenching operation, an optimum cooling rate and homogeneous temperature distribution on hot blanks towards the achievement of the martensitic microstructure transformation as well as high mechanical properties. This study dispersed Al2O3 nanoparticles from the range of 0.2 to 1.0% volume concentration with an average diameter of 13 nm into three volume percentages of water to ethylene glycol such as 60%:40%, 50%:50%, and 40%:60% by using the two-step preparation method. The two main parameters in cooling rate performance are thermal conductivity and dynamic viscosity. The heat transfer distribution of the hot blanks with nanocoolant and chilled water are simulated for transient thermal analysis in finite element simulation via ANSYS to evaluate the enhancement of convection heat transfer coefficient and determine the optimum cooling rate of cooling system in HPF tool. The simulation data were then compared with experimental findings for validation purpose. It was found that the highest enhancement of thermal conductivity was observed to be 10% higher than base fluid for 1.0% volume concentration of Al2O3 at 55 °C in 60%:40% (W/EG). However, the highest enhancement of dynamic viscosity was measured to be 39% for 1.0% volume concentration of Al2O3 in 40%:60% (W/EG) at 25 °C. The convective heat transfer coefficient of 1.0% concentration in 60%:40% (W/EG) at 25 °C is enhanced by 25.4% better than that of 50%:50% and 40%:60% (W/EG) base fluid. Therefore, this study recommends the use of Al2O3 in 60%:40% (W/EG) mixture with volume concentration of Al2O3 less than 1.0% for application in cooling channel of HPF dies. It was also evident that the pattern of the temperature distribution of the finite element analysis model was in agreement with the experimental results. The tensile strength and Vickers hardness values of the hot pressed parts were evaluated to be approximately 1,550 MPa and 588 HV, respectively. In conclusion, nanocoolant as cooling fluid with higher convection heat transfer coefficient compared to the chilled water can reduce the quenching time of HPF process.